The Relationship between the Students’ Motivation and the Reading Comprehension at the Tenth Grade on the first Semester of SMKN 8 Bekasi in the 2020/2021 Academic Year - Syifa Oktavia Irfany; Burhayani (UICELL, 2020)
ABSTRACT The objective of this study is to know the relationship between students' motivation and the reading comprehension. This research is a quantitative research approach, and the methodology that the writer use is correlational research. The population of this research are the tenth-grade students of SMKN 8 Bekasi that have ten classes. The writer only takes one class (Accountant 2) with 33 students by using random sampling from the population. In collecting the data, the writer uses a questionnaire to measure students' motivation which is adopted from R.C. Gardner, Attitude Motivation Test Battery (AMTB) and to measure students reading comprehension ability the writer uses reading comprehension test. The data are collected and calculated by using Pearson Product Moment Coefficient Correlation. The writer finds that the ro 0,842 is higher than rt 0,34 (ro > rt ) from the result of calculating by using the Pearson Product Moment Coefficient Correlation. The result can be concluded that the research hypothesis Ho is rejected and Hi accepted. From the conclusion, it can be proved that the verbal hypothesis has been accepted. Then, ro 0,842 it means that xy is higher than zero points. Thus, the statistical hypothesis has been accepted too. Those can prove that there is a relationship between the students’ motivation and the reading comprehension at the tenth grade in the first semester at the SMKN 8 Bekasi of the 2020/2021 academic year. The research result, the writer hopes that this research is useful for the English teacher and reader. Keywords: Motivation, Correlational Study, AMTB